Gambaran Tingkat Pengetahuan Swamedikasi Penggunaan Obat Analgetik Antipiretik pada Masyarakat Kelurahan Kenanga Kota Tangerang - Haryanto, Kusno; Marlindasari, Liskha (Jurnal Medika Farmaka, 2024)
One of the reasons many people do self-medication is the development of information technology via the internet and mass media about medicine. Another reason is to save costs, save time, and drugs for disorders such as pain and fever are easily found in pharmacies and drug stalls. The most widely used drug in self-medication is Paracetamol. The indication of Paracetamol is as an antipyretic analgesic, side effects of Paracetamol such as nausea, dizziness, vomiting, and long-term use can cause liver damage. This type of research uses descriptive quantitative. Quantitative research is a technique used to process data in the form of numbers, either as a result of measurement or conventional results. This study describes the level of knowledge of self-medication using antipyretic analgesic drugs in the community of Kenanga Village, Cipondoh, Tangerang City. The population in this study was the people of Kenanga Village, Cipondoh, Tangerang City RT 02 RW 01 as many as 302 people. Determination of the number of respondents using the Slovin rule so that the number of samples obtained was 80 respondents. The results showed that 49 respondents (61.25%) had good knowledge, 27 respondents (33.75%) had sufficient knowledge and 4 respondents (5%) had poor knowledge